Model Matematika Penyebaran Online Compulsive Buying Disorder - Lovira Puspita; Arnellis Arnellis (Journal of Mathematics UNP, 2023)
ABSTRACT Online compulsive buying disorder is a disorder of impulse control when shopping online, so that a person becomes uncontrollable when shopping online and is done repeatedly with a large number of purchases and not so useful. The purpose of this study is to analyze the mathematical model of the spread of online compulsive buying disorder. The method used is the descriptive method. Based on the analysis of the mathematical model of the spread of online compulsive buying disorder, one equilibrium point was obtained, where all eigenvalues of the Jacobi matrix were negative, so that the equilibrium point of the mathematical model of the spread of online compulsive buying disorder was stable asymptotic. This suggests that the spread of online compulsive buying behavior will go towards the equilibrium point over time.